Implantação e avaliação do MOOC: pesquisa em base de dados de enfermagem - Gomes, Juliana Invencao [UNIFESP] (2018)
Introduction: Given the benefits of the application of Information and Communication Technology (ICT) in the different scenarios of the nurses' work, it is necessary that computer skills be included in both their training and postgraduate nursing education. In this perspective, the Massive Open Online Courses (MOOC) constitute a facilitating element in the training of professionals in the health area. Objective: To propose the development of a MOOC based on the competences in informatics in nursing required by the Technology Informatics Guiding Education Reform (TIGER). Methods: This is an interventional, quasi experimental and piloty study, with a quantitative approach, consisting of the following steps: definition of educational objectives, pedagogical architecture elaboration, instructional content production, course implementation and, finally, satisfaction of participants evaluation. Results: o xMOOC Bibliographic Research in Nursing Databases aimed at training nurses to perform bibliographic research in electronic databases, in an autonomous way, contemplating recommendations for content approaches related to the development of informational skills in postacademic training. Satisfaction assessment was performed by 25 course participants and achieved positive results involving all aspects related to the course objectives, content, responsible staff, availability, evaluation, AVEA and perceived learning investigated. Final Considerations: When proposing a MOOC that allows the democratization of education and that has the student as a selfregulating agent of the learning process, it is hoped to potentialize the educational process expansion mediated by computational technologies.